Nano-Encapsulated Ebastine Niosomal Transdermal Nanogel: QBD Model for Allergy Treatment and Evaluation - Bhushan R. Rane; Aditi P. Padave; Ashish S. Jain (Biology and Life Sciences Forum)
Niosomes are a stable vesicular system composed of non-ionic surfactants and cholesterol, offering advantages such as enhanced stability and controlled drug release. In this study, a niosomal nanogel loaded with Ebastine was developed to improve patient compliance in treating skin allergic reactions. Thin-film hydration was employed to prepare niosomes using cholesterol, Span 60, Tween 80, and Ebastine, optimized via Box–Behnken experimental design. A dispersion method incorporating Carbopol 934 was utilized to create a niosomal gel, ensuring effective therapeutic outcomes. The formulation exhibited high drug entrapment efficiency (84.19%), a zeta potential of −27 mV, and vesicle sizes ranging from 100 to 300 nm. Evaluation included FTIR for drug–excipient compatibility, pH assessment, in vitro drug release studies, and stability testing, all yielding acceptable results. The encapsulation of Ebastine within niosomes is driven by critical physicochemical interactions between the drug, cholesterol, and surfactants. These interactions influence the stability, encapsulation efficiency, and release profile of the drug from the niosomal bilayer. Microbial studies indicated significant antimicrobial activity against S. aureus, underscoring its potential as an effective transdermal treatment for skin allergies.